Germinated and Ungerminated Seeds Extract from Two Lupinus Species: Biological Compounds Characterization and In Vitro and In Vivo Evaluations. (20th December 2016) - Andor, Bogdan; Danciu, Corina; Alexa, Ersilia; Zupko, Istvan; Hogea, Elena; Cioca, Andreea; Coricovac, Dorina; Pinzaru, Iulia; Pătrașcu, Jenel Marian; Mioc, Marius; Cristina, Romeo Teodor; Soica, Codruta; et al.
Abstract : In recent years, nutraceuticals attracted a great amount of attention in the biomedical research due to their significant contribution as natural agents for prevention of various health issues. Ethanolic extracts from the ungerminated and germinated seeds of Lupinus albus L. and Lupinus angustifolius L. were analyzed for the content in isoflavones (genistein) and cinnamic acid derivatives. Additionally, the extracts were evaluated for antimicrobial, antiproliferative, and anti-inflammatory properties, using in vitro and in vivo tests. Germination proved to be a method of choice in increasing the amount of genistein and cinnamic acid derivatives in both Lupinus albus L. and Lupinus angustifolius L. seeds. Biological evaluation of all vegetal extracts revealed a weak therapeutic potential for both ungerminated and germinated seeds.